Association of Neuregulin-4 Levels and Body Mass Index with Hyperandrogenism in Polycystic Ovary Syndrome Patients - Ghalib, Mustafa M.; Rasheed, Manal K.; Al-Naddawi, Afraa M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a common endocrine and metabolic disease that affects approximately 15% of women of childbearing age worldwide. It is one of the causes of infertility and is characterized by hirsutism, acne, persistent or interrupted anovulation, and hyperandrogenemia. Neuregulin-4 (NRG-4) is an adipokine hormone from the protein neuregulin family. Its level is greater in PCOS than in control women, and Neuregulin-4 is linked to body fat percentage and liver fat, as well as insulin resistance (IR).Objectives: To estimate the serum NRG-4 levels in women diagnosed with (PCOS), to compare it with non-PCOS healthy control, and to explore the effect of hyperandrogenism on the obtained result.Methods: A case-control study was conducted in the Gynaecology and Infertility Clinics in Kut-AlZahraa Hospital, Medical City, from September to December 2022. The study included 120 women aged 18-42 years, 60 of whom were diagnosed with polycystic ovaries, and the other 60 were in the control group.Results: Women with PCOS had a significantly higher NRG-4, LH, LH/FSH ratio, testosterone, free testosterone, and dehydroepiandrosterone sulfate (DHEA-S) than the control groups. In this study, NRG-4 was significantly higher in obese and overweight PCOS women than in normal-weight women.Conclusion: The mean serum NGR-4 concentration is significantly increased in women with PCOS and could be a part of metabolic syndrome. NGR-4 levels were associated with obesity and hyperandrogenism (testosterone, free testosterone, and DHAES) and may have a role in the development of PCOS.